GNU/Linux application programming - Jones, M. Tim (Charles River Media, 2005)
The wide range of applications available in GNU/Linux includes not only pure applications, but also tools and utilities for the GNU/Linux environment. GNU/Linux Application Programming takes a holistic approach to teaching developers the ins-and-outs of GNU/Linux programming using APIs, tools, communication, and scripting. Covering a variety of topics related to GNU/Linux application programming, the book is split into six parts: The GNU/Linux Operating System, GNU Tools, Application Development, Advanced Topics (including communication and synchronization and distributed computing), Debugging GNU/Linux Applications, and Scripting. The book introduces programmers to the environment from the lowest layers (kernel, device drivers, modules) to the user layer (applications, libraries, tools), using an evolutionary approach that builds on knowledge to cover the more complex aspects of the operating system. Through a readable, code-based style developers will learn about the relevant topics of file handling, pipes and sockets, processes and POSIX threads, inter-process communication, and other development topics. After working through the text, theyill have the knowledge base and skills to begin developing applications in the GNU/Linux environment.